2014
DOI: 10.17221/315/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term chemical fertilization on trends of rice yield and nutrient use efficiency under double rice cultivation in subtropical China

Abstract: A long-term (33 years) experiments were conducted to investigate the effect of chemical fertilization on rice yield, yield trends, soil properties, agronomic efficiency of applied nutrients and nutrient balance for the double rice cropping systems in subtropical China. The treatments were different combinations of N, P and K fertilizers (N, NP, NK and NPK), double dose of recommended NPK (2NPK) and no fertilizer control (control). Compared with no fertilizer control, all fertilization treatments had no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These values are similar to those reported in paddy rice soils of subtropical China [40]. Some previous studies have linked such high TN levels and variations to long-term fertilizer applications [41,42]. In 2020 a local newspaper article (printed in Swahili) pointed out that the farmers in the surveyed area mentioned to researchers that they were using high amount of fertilizers and other agricultural inputs but rice production was not improving [43].…”
Section: Soil Macro-and Micro-nutrientssupporting
confidence: 80%
“…These values are similar to those reported in paddy rice soils of subtropical China [40]. Some previous studies have linked such high TN levels and variations to long-term fertilizer applications [41,42]. In 2020 a local newspaper article (printed in Swahili) pointed out that the farmers in the surveyed area mentioned to researchers that they were using high amount of fertilizers and other agricultural inputs but rice production was not improving [43].…”
Section: Soil Macro-and Micro-nutrientssupporting
confidence: 80%
“…In a similar study, Bi et al (2014) observed that the sole application of chemical fertilizers lead to reduced rice productivity and reduced soil productivity on long-run.…”
Section: Soil Fertilization At Kalimbeza Rice Project Fieldmentioning
confidence: 88%
“…Although, unsustainable intensive rice cultivation pose a serious threat to ecological sustainability of rice environment and soil productiveness (Nwilene et al, 2008), the rice producers are less motivated to practice sustainable rice farming because of shortterm goals and economic aspects which drive them into fast profit making farming practices. The farmers practice intensive rice mono-cropping which has been proven to account for the major decline in rice production over long run as a result of soil deterioration, low fertility, low organic matter and low nutrients availability (Yan et al, 2007;Bi et al, 2014). In a separate report, Neeson et al (2005) noted that rice production mainly by mono-cropping increases nitrogen loses from the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, Jayne et al (2014) propose that agricultural and rural development strategies need to more anticipate the implications of rapidly changing land. Furthermore, a number of researches are conducted in investigating on the long-term effects of single fertilizers upon the soil fertility and productivity (Bi et al, 2014;Suman et al, 2016;Venkatesan et al, 2004). Following Kumar and Yaday (2008), the yield response of grains further to a direct nitrogen fertilizer supply would decline over the long period.…”
Section: Jel Classification: C22 Q01 Q15mentioning
confidence: 99%